59.1.578 problem 594

Internal problem ID [9750]
Book : Collection of Kovacic problems
Section : section 1
Problem number : 594
Date solved : Monday, January 27, 2025 at 06:13:52 PM
CAS classification : [[_2nd_order, _with_linear_symmetries]]

\begin{align*} x^{2} \left (-x^{2}+2\right ) y^{\prime \prime }-x \left (3 x^{2}+2\right ) y^{\prime }+\left (-x^{2}+2\right ) y&=0 \end{align*}

Solution by Maple

Time used: 0.005 (sec). Leaf size: 19

dsolve(x^2*(2-x^2)*diff(y(x),x$2)-x*(2+3*x^2)*diff(y(x),x)+(2-x^2)*y(x)=0,y(x), singsol=all)
 
\[ y = \frac {x \left (c_{2} \ln \left (x \right )+c_{1} \right )}{x^{2}-2} \]

Solution by Mathematica

Time used: 0.265 (sec). Leaf size: 51

DSolve[x^2*(2-x^2)*D[y[x],{x,2}]-x*(2+3*x^2)*D[y[x],x]+(2-x^2)*y[x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\[ y(x)\to \sqrt {x} (c_2 \log (x)+c_1) \exp \left (-\frac {1}{2} \int _1^x\left (\frac {4 K[1]}{K[1]^2-2}-\frac {1}{K[1]}\right )dK[1]\right ) \]